International Debt Statistics 2022 - World Bank (Washington, DC: World Bank, 2021)
International Debt Statistics (IDS), a long-standing annual publication of the World Bank, features external debt statistics and analysis for the 123 low- and middle-income countries that report to the World Bank Debtor Reporting System. IDS 2022 includes (1) an overview analyzing global trends in debt stocks of and debt flows to low- and middle-income countries within the framework of aggregate capital flows (debt and equity); (2) an evaluation of the volume of debt service deferred through the Debt Service Suspension Initiative (DSSI) in 2020 and the 2021 extension for participating eligible countries, as well as borrowing trends and debt service costs for DSSI-eligible countries that did not participate in the initiative; (3) tables and charts detailing debtor and creditor composition of debt stock and flows, terms of new commitments, and maturity structure of future debt service payments and debt burdens, measured in relation to gross national income and export earnings for each country; (4) one-page summaries per country, plus global, regional, and income group aggregates showing debt stocks and flows, relevant debt indicators, and metadata for six years (2010 and 2016–20); and (5) a user guide describing the tables and content, definitions and rationale for the country and income groupings used in the report, data notes, and information about additional resources and comprehensive data sets available to users online. Unique in its coverage of the important trends and issues fundamental to the financing of low- and middle-income countries, IDS 2022 is an indispensable resource for governments, economists, investors, financial consultants, academics, bankers, and the entire development community. For more information on IDS 2022 and related products, please visit the World Bank’s Data Catalog at https://datacatalog .worldbank.org/dataset/international-debt -statistics.